THE EFFECT OF LEARNING CELL TOWARDS STUDENTS’ CREATIVITY IN READING - Teddysetiadi, Teddysetiadi (Universitas Pendidikan Mandalika, 2016)
The aims of this research was to find out whether learning cell has an effect toward students’ reading ability at the eight year students of SMPN 4 Lingsar Lombok Barat in The Academic Year of 2016/2017. This research was an experimental research consists of four classes as population and one class taken as sample by using purposive sampling technique. In sustaining the research result, the data was collected by using a reading test in the form of multiple choices and creativity questionnaires. Then, the data were analyzed by using statistic and descriptive analysis. Based on The data analysis, it can be found that the average score of experimental group was 61.72 for the reading test meanwhile for the creativity mean score was 14.05. To know the correlation level the researcher used r-test in which the result was 1.059 in other word it has a strong correlation level. Then to know the significance correlation of the result, the score was identified by using t-test, the result shows that t0 (t-obtain) > tt (t-table) or 17.738 > 1.69. Thus, it can be concluded that learning cell has a significant effect toward the students’ reading at SMPN 4 Lingsar Lombok Barat in The Academic Year of 2016/2017.